Buddhist Management Principles as a Driver of Social Entrepreneurship Success in Indonesia - Franky Okto Bernando; Sari Rahaju; Pringgondani Pringgondani (International Journal of Applied Business and International Management, 2026)
Social entrepreneurship in Indonesia suffers a high failure rate, with roughly 60% of social startups collapsing within three years owing to weak managerial capacity and the difficulty of balancing profit with social mission. This study aims to examine the influence of Buddhist Management Principles (BMP) on the success of social entrepreneurship in Greater Jakarta. BMP is operationalized into five dimensions, namely Ethics (Sila), Wisdom (Panna), Servant Leadership (Metta-Karuna), Ecological Sustainability (Ahimsa), and Equanimity (Upekkha), while success is measured through financial sustainability, social innovation, stakeholder empowerment, and environmental preservation. Using an explanatory quantitative design, data from 150 social-enterprise actors selected by purposive sampling were analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that BMP exerts a positive and significant effect on social-entrepreneurship success (b = 0.826; t = 13.836; p 0.001; R-squared = 0.683; f-squared = 2.152). The study concludes that Buddhist spiritual values can be translated into a measurable managerial framework. It is suggested that practitioners and educators embed these value-based principles in curricula and social-enterprise support policy.